Avaliação de mudanças no sistema educacional e seus resultados: o caso dos ciclos na região metropolitana de Porto Alegre - Tanise Brandão Bussmann (2014)
Brazilian education is being analyzed in the last years based on different perspectives. One of the recent changes, with the Education Law of Guidelines and Basis (1996), was the suggestion of implementation of a system of non-reprobation, the cycles, in the schools of basic education. This system of educational evaluation is distinct from the traditional one, using a more embracing evaluation and a distinct periodization, bringing changes to the Brazilian Educational System. Since just a portion of school had adopted this model, we will seek to observe which are the main differences between students and schools from both systems. To do so, it is used a hierarquical linear model and the database from the Brazilian System of Basic Education, Scholar Census, Demographic Census and Finances of Brazil. The period of analysis will be from 1999 to 2011. There is a bigger emphasis to the metropolitan region of Porto Alegre, since there was a massive adhesion to cycles do to a municipal law in Porto Alegre. The performance of individuals that study in school where the system of cycles has been adopted were slightly better than the others. The students from cycles schools in the metropolitan region of Porto Alegre had a much smaller performance. It was also possible to observe the differences between the students, mainly in the endowment, in the differential decomposition. Modifying the basic unit to school, the difference kept significant to the ninth year according to the endowment factor.